Stability Analysis of Explicit and Implicit Stochastic Runge-Kutta Methods for Stochastic Differential Equations - Adam, Samsudin; Norhayati, Rosli; Amalina Nisa, Ariffin (IOP Publishing, 2017)

(untitled)
This paper concerns to the stability analysis of explicit and implicit stochastic Runge-Kutta methods in approximating the solution of stochastic models. The stability analysis of the schemes in mean-square norm is investigated. Linear stochastic differential equations are used as test equations to demonstrate the efficiency of the proposed schemes.